2022
DOI: 10.3389/fmicb.2022.981987
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing rhizosphere microbial communities associated with tolerance to aboveground herbivory in wild and domesticated tomatoes

Abstract: Root-associated microbial communities are well known for their ability to prime and augment plant defenses that reduce herbivore survival or alter behavior (i.e., resistance). In contrast, the role root microbes play in plant tolerance to herbivory, an evolutionarily sustainable alternative to resistance, is overlooked. In this study, we aimed to expand our limited understanding of what role rhizosphere microbial communities play in supporting tolerance to insect damage. Using domesticated tomatoes and their w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“… Pantigoso et al (2020) reported that environmental stress has a significant effect on the rhizosphere soil microflora of cultivated and wild potato plants. Besides, the wild and cultivated tomatoes also showed microbial community structural differences caused by soil properties and environmental pressures ( Tronson et al, 2022 ). Similarly, wild and cultivated P. australis also show different responses to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“… Pantigoso et al (2020) reported that environmental stress has a significant effect on the rhizosphere soil microflora of cultivated and wild potato plants. Besides, the wild and cultivated tomatoes also showed microbial community structural differences caused by soil properties and environmental pressures ( Tronson et al, 2022 ). Similarly, wild and cultivated P. australis also show different responses to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that plant roots shape and benefit from associated rhizosphere bacterial communities ( Edwards et al, 2015 ; Perez-Jaramillo et al, 2018 ). What’s more, rhizosphere bacterial communities play a role in supporting pest tolerance ( Tronson et al, 2022 ) and increasing yield ( Su et al, 2022 ). Therefore, the study of rhizosphere bacterial communities is important for the transformation of pollutants, plant health and agricultural production in lake ecosystems.…”
Section: Introductionmentioning
confidence: 99%